Evaluations of Virtual Defendants With Depleted or Rich Contextual Information - Bethany Muir; Eryn Newman; Meredith Rossner (Tilburg Law Review)
With the rapid flip to virtual courts in 2020, justice contexts changed dramatically. Suddenly, the courtroom looked very different: Courtroom architecture was replaced with personal devices and people were constrained to presenting themselves through modalities such as video and audio. Remote communications also introduced other extralegal factors, including background cues indicating the location from which the attendee is joining, which has raised concerns regarding the potential for such cues to jeopardize the fairness of a trial. In this paper we present a series of experiments to test the impact of presentation modality and visual background cues. Across two experiments (total N = 608), we varied whether defendants appeared in front of custodial, home, or neutral contextual backgrounds. We also varied whether defendants appeared via video or a static image. We asked participants to rate perceived guilt and trustworthiness (or dangerousness in Experiment 2) of the defendant. We found that custodial backgrounds led to less favorable evaluations than home and neutral contextual backgrounds. Further, if defendants appeared with a static image, they were evaluated less favorably than if they appeared via video. This research provides insights into how access to contextual backgrounds and dynamic social cues may influence impressions in virtual justice contexts and raises questions about equity, policy, and procedure.